2020
DOI: 10.14407/jrpr.2020.45.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Doses in Children from Radioiodine following the Accident at the Fukushima Daiichi Nuclear Power Plant

Abstract: Background: Huge amounts of radionuclides were released into the environment due to the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident, which caused not only serious contamination on the ground, but also radiation exposure to the public. One problem that remains in performing the dose estimation is the difficulty of estimating the internal thyroid dose due to the intake of radioiodine (mainly, 131 I) because of limitations to the human data available. Materials and Methods:The relevant papers were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…The results of the research during this 9-y period indicated that the estimated radiation doses to the residents were to be low in general, and the residents' future radiation-induced risk was considered low (UNSCEAR 2014). However, as we have pointed out (Kim et al 2016a and c; Kim et al 2020; Kim and Kurihara 2020), further studies are still needed to improve the dose assessment; in particular, the dose assessment for internal thyroid exposure from the short-lived radionuclides (e.g., 131 I, 132 Te- 132 I, and 133 I). The greatest obstacle has been the shortage of direct human measurements at the early phase when the traces of 131 I (the main contributor to the internal thyroid dose) were detectable.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the research during this 9-y period indicated that the estimated radiation doses to the residents were to be low in general, and the residents' future radiation-induced risk was considered low (UNSCEAR 2014). However, as we have pointed out (Kim et al 2016a and c; Kim et al 2020; Kim and Kurihara 2020), further studies are still needed to improve the dose assessment; in particular, the dose assessment for internal thyroid exposure from the short-lived radionuclides (e.g., 131 I, 132 Te- 132 I, and 133 I). The greatest obstacle has been the shortage of direct human measurements at the early phase when the traces of 131 I (the main contributor to the internal thyroid dose) were detectable.…”
Section: Introductionmentioning
confidence: 99%
“…After the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident in March 2011, a great effort has been made to assess the radiation exposure doses of residents of Fukushima Prefecture by many Japanese scientists and international bodies (Ishikawa 2017, 2020; Kurihara 2018; Kim and Kurihara 2020; WHO 2012; UNSCEAR 2014; IAEA 2015). These results would provide the scientific basis to estimate the future radiation-associated health effects of the prefecture's residents.…”
Section: Introductionmentioning
confidence: 99%